1959
DOI: 10.1152/jappl.1959.14.5.717
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary surface tension

Abstract: The surface tension of the lung decreases markedly on compression resulting from deflation, as calculated from P-V data, and follows a force-area path very similar to that of several mucus surfaces. With changes in surface area of less than 50%, lung extract and mucus bubble surfaces are mechanically reversible. For decrease in area greater than 50%, surface tension approaches a lower limiting tension of 10–15 d/cm. On re-expansion of the surface, an upper limiting tension of 40–50 d/cm is approached. Hysteres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
2
3

Year Published

1962
1962
1983
1983

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(52 citation statements)
references
References 0 publications
1
46
2
3
Order By: Relevance
“…Surface activity of saline extracts from 3 g of pooled minced lung tissue was measured with a modified Wilhelmy balance as described by CLEMENTS et al and modified by others [6,10,271. The minimum surface tension during compression of the surface was recorded after 2 % hours of cycling (10 cycles) or when three consecutive cycles had shown the same minimum surface tension.…”
Section: Methodsmentioning
confidence: 99%
“…Surface activity of saline extracts from 3 g of pooled minced lung tissue was measured with a modified Wilhelmy balance as described by CLEMENTS et al and modified by others [6,10,271. The minimum surface tension during compression of the surface was recorded after 2 % hours of cycling (10 cycles) or when three consecutive cycles had shown the same minimum surface tension.…”
Section: Methodsmentioning
confidence: 99%
“…4). Furthermore, although CTV-ventilated hyperthermic rats did develop alveolar instability in association with a diminished amount of airway surfactant, even in this circumstance, the total quantity of airway DSPC present is theoretically sufficient to form a monomolecular film over the entire alveolar surface at functional residual capacity (15); the amount of DSPC present in the 1,OOO-g supernatant fraction is not enough for this purpose. An inhibitor, or inactivator, of surfactant could decrease alveolar stability without diminishing the amount of airway surfactant and this could explain our results.…”
mentioning
confidence: 93%
“…A number of studies have been presented on the chemical nature and metabolism of this lung surfactant. It has generally been accepted that so-called dipalmitoyllecithin, one of the molecular species of lecithin, in the lung and alveolar wash is the principal compo nent of the surfactant (Pattle 1958, Brown et al 1959, Klaus et al 1961, Avery 1959. Morgan et al (1965) reported that alveolar lipids in dog pulmonary wash contained significant amounts of phosphatidyldimethylethanolamine which might contribute to the formation of dipalmitoyllecithin with methyltransferase.…”
mentioning
confidence: 99%